Geological Sites as a Safe Resort for Post-COVID-19 Tourism: The Case of Al Jabal Al Akhdar, Oman - AFIFI, Galal M. H.; NEGM, Maged. M. F. (Journal of Environmental Management and Tourism; Vol 11 No 6 (2020): JEMT Volume XI, Issue 6(46) Fall 2020DO - 10.14505/jemt.v11.6(46).23, 2020)
COVID-19 is undoubtedly an unprecedented crisis that hits tourism heavily. To date, it is unconfirmed when tourism businesses can reopen again. However, official and unofficial tourism entities proclaim that tourism should resume as soon to save the massive investments and the millions of jobs in this sector. It is also agreed that Post-COVID-19 tourism will significantly differ from the Pre-COVID-19 era, where both tourists’ characteristics and tourist product features will witness major changes. In this context, this research suggests geo-tourism as a potential safe resort for the Omani tourism business, assuming that the features of this type of tourism will meet the requirements of Post-COVID-19 tourism. The research investigates Al Jabal Al Akhdar as a model case for this assumption.